Teori Perkembangan Jean Piaget dan Implikasinya Dalam Perkembangan Anak Sekolah Dasar - Nafiah Nur Shofia Rohmah; Murfiah Dewi Wilandari; Darsinah Darsinah (Peneliti.net, 2022)
The goal of this study is to determine how Jean Piaget's theory of development and its effects on elementary school students' development. A qualitative descriptive method with a literature study approach was used as the research methodology. Books, journals, articles, and other scientific works that are pertinent to the topic under study serve as the sources of information for the literature study. The findings demonstrated that elementary school-aged children's cognitive development varies depending on their age. According to Piaget's cognitive theory, children's cognitive development in the elementary school years is in the concrete operational phase (ages 7 to 11), which is a stage in which kids can think logically, rationally, scientifically, and objectively about something concrete or real. As a result, the teacher must present learning material that is empirical (real), not abstract or fictitious, during teaching and learning activities. The learning process must be grounded in reality, for instance, by providing concrete examples of the material being studied (modeling) and engaging in hands-on practice (experiments).